Persepsi Siswa terhadap Nilai-nilai Moderasi Beragama dalam Pendidikan Islam melalui Pembelajaran Al-Qur’an - Muchtar, Nicky Estu Putu; Safitri, Laily Nur (Universitas Islam Tribakti Lirboyo Kediri, 2025)
The strawberry generation is a young generation that is fragile in the face of challenges but creative, active, and critical. In Islamic Education, their understanding of religious moderation is important to prevent extremism and intolerance. This study examines the perception of students of the strawberry generation of religious moderation in learning the Qur'an, which was carried out at SMA Negeri 1 Lamongan using qualitative methods and case study approaches. The study results show that applying religious moderation values has gone well. PAI teachers play a role in teaching the values of tawasuth (moderate), tasamuh (tolerance), tawazun (balanced), and i'tidal (fair). Students' perceptions tend to be positive, and they understand the importance of a moderate, tolerant, and balanced attitude in religious life. Learning the Qur'an contributes significantly to shaping this understanding. A more interesting learning strategy is needed so that the values of religious moderation are more straightforward to accept and practice in student life.